Keragaan vegetatif dan generatif pada fase pembungaan awal kelapa Genjah kopyor asal kultur embrio di Bogor, Jawa Barat - Muhammad Eko Riyo Bayu PRASETYO; Imron RIYADI; Sumaryono SUMARYONO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2022)
The performance of kopyor Dwarf coconuts from embryo culture in the field has not been reported. This study was conducted to determine the difference in vegetative and generative performances of three fruit color phenotypes (brown, green, and yellow) of kopyor Dwarf coconuts in the first year after the first flower appeared. The coconuts were planted in Bogor, West Java at 260 masl with average temperature 26.9 ºC and average rainfall 4,300 mm/year. Each color phenotype was represented by 20 kopyor coconut trees from the same planting date that had not been flowering yet. When the first flowers appeared, Kopyor Brown Dwarf (KBD) had 14.6 fronds, while Kopyor Yellow Dwarf (KYD) and Kopyor Green Dwarf (KGD) had 15.5 and 17.1 fronds respectively. Other vegetative components when the first flower appeared were not significantly difference among the three color phenotypes such as stem girth (90.7-99.2 cm), stem height (18.6-23.9 cm), frond length (3.9-4.2 m) and canopy diameter (5.8-6.1 m). KBD coconuts started flowering faster than that of KGD and KYD. The numbers of flowers formed in the first year of flowering were 15 to 17 flowers per tree. There was an initial sharp decrease in the survival of young fruits, but this levelled off after 2-3 months. On average 18-22 fruits per bunch at flowering decreased to 5-6 fruits per bunch at maturity. The survival of fruits in KGD (6.2 fruits per bunch) was higher than KBD (4.0 fruits) and KYD (4.5 fruits) at 11 months after flowering. The average fruit size and weight of brown phenotype were higher than green and yellow phenotypes. The mature brown fruits had a lower husk percentage, but higher shell and fruit meat percentages than those of the green and yellow fruits.[Keywords: fruit color phenotype, kopyor Dwarf coconut, fruit abortion, fruit quality] AbstrakKeragaan kelapa Genjah kopyor asal kultur embrio di lapang belum pernah dilaporkan. Penelitian ini dilakukan untuk mengamati perbedaan keragaan vegetatif dan generatif tiga varietas kelapa Genjah kopyor yang berbeda dari warna buah (coklat, hijau dan kuning) pada tahun pertama sejak bunga pertama muncul. Kelapa tersebut ditanam di Bogor, Jawa Barat pada 260 mdpl dengan rerata suhu 26,9 ºC dan curah hujan 4.300 mm/tahun. Tiap fenotipe warna diwakili oleh 20 pohon kelapa kopyor berumur sama yang belum berbunga. Pada saat bunga pertama muncul, kelapa Genjah Coklat Kopyor (GCK) memiliki 14,6 pelepah daun, sedangkan Genjah Kuning Kopyor (GKK) dan Genjah Hijau Kopyor (GHK) berturut-turut memiliki 15,5 dan 17,1 pelepah. Parameter vegetatif lain ketika bunga pertama muncul tidak berbeda nyata antar fenotipe warna misalnya lingkar batang (90,7-99,2 cm), tinggi batang (18,6-23,9 cm), panjang pelepah (3,9-4,2 m) dan diameter tajuk (5,8-6,1 m). GCK mulai berbunga lebih cepat dibandingkan dengan GHK dan GKK. Jumlah bunga yang terbentuk selama satu tahun pertama pembungaan adalah 15 sampai 17 bunga per pohon. Jumlah buah muda yang bertahan hidup menurun tajam pada awal, namun relatif stabil setelah 2-3 bulan. Rata-rata terbentuk sebanyak 18-22 buah per tandan pada awal pembungaan dan menurun menjadi 5-6 buah per tandan saat dewasa. Buah yang bertahan hidup pada GHK (6,2 buah per tandan) lebih tinggi dibanding GCK (4,0 buah) dan GKK (4,5 buah) pada umur 11 bulan setelah bunga mekar. Rata-rata ukuran dan bobot buah fenotipe coklat lebih tinggi daripada fenotipe hijau dan kuning. Buah kelapa GCK mempunyai persentase sabut yang lebih rendah, tetapi persentase tempurung dan daging buah yang lebih tinggi dibandingkan dengan buah kelapa GHK dan GKK.[Kata kunci: fenotipe warna buah, kelapa Genjah kopyor, kerontokan buah, kualitas buah]